SYSTEM OF INSTITUTIONAL PROVISION OF FUNCTION OF ORGANIZATIONAL ANG LEGAL FORM ON RURAL TERRITORIES - Shelenko, D.I.; Balaniuk, I.F.; Savka, M.V.; Kostiuk, B.A. (The actual problems of regional economy development, 2018)
The article is aimed at researching elements of the system of institutional providing for the functioning of agricultural enterprises. The attention has been paid to the theoretical basis of the system of institutional providing, which should include the following blocks: motivation, methodology of state influence, competitive relations; financial, regulatory and control. The necessity of applying a systematic approach in the management of agricultural enterprises has been proved by the condition of information about the traditions and values of the peasants, which are formed using the social rebirth and development of the Ukrainian village and the concept of a market economy, which is based on increasing the prestige of life and work in the countryside, in particular in the agricultural enterprise.